PENGARUH LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATAN KECERDASAN EMOSIONAL SISWA KELAS X IPS SMA NEGERI 5 PEKANBARU - Hesti Novela Hesti Novela; Elni Yakub Elni Yakub; Zulfan Saam Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims 1) To reveal the emotional intelligence of students before being held counseling services group 2) To know the process of implementing the guidance of the group to improve the emotional intelligence of students 3) To reveal the emotional intelligence of students after being given guidance services group 4) To see whether there are differences in intelligence Emotional students before and after group counseling 5) To determine the effect of group counseling services to increase emotional intelligence of students. Data collection tools such as emotional intelligence questionnaire. Subjects were students of class X IPS SMAN 5 Pekanbaru totaling 147 people. The samples using purposive sampling and the sample in this study as many as 30 people. Emotional intelligence picture before the given group counseling services are in the low category of 83.3%, the category was 16.7% and amounted to 0% higher category. Picture of emotional intelligence of students after a given group counseling services are in high category of 13.3%, medium category by 80% and 6.7% lower categories. Based on the calculation of the correlation coefficient is 0.50 and the determinant coefficient = 0.25 it means the donation of 25% of group counseling. It can be seen larger than (10.07> 2,000) so that Ha is accepted. Means that there are significant group counseling to improve emotional intelligence class X IPS SMAN 5 Pekanbaru TA. 2014/2015.Key Words: Guidance Services Group, Emotional Intelligent